2013
DOI: 10.1039/c3cc44177f
|View full text |Cite
|
Sign up to set email alerts
|

A one-step low temperature processing route for organolead halide perovskite solar cells

Abstract: Organolead trihalide perovskite solar cells based upon the co-deposition of a combined Al2O3-perovskite layer at T < 110 °C are presented. We report an average PCE = 7.2% on a non-sintered Al2O3 scaffold in devices that have been manufactured from a perovskite precursor containing 5 wt% Al2O3 nanoparticles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
171
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 222 publications
(175 citation statements)
references
References 17 publications
(17 reference statements)
1
171
0
2
Order By: Relevance
“…− cage have formal electronic configurations of Pb: 5d 10 6s 2 6p 0 and I: 5p 6 . As can be seen from the colour coding, the valence band maximum consists of approximately 70% I 5p and 25% Pb 6s (the Pb 6s forms a band centred around −8 eV), while the conduction band consists a mixture of Pb 6p and other orbitals.…”
Section: A Band Structurementioning
confidence: 99%
“…− cage have formal electronic configurations of Pb: 5d 10 6s 2 6p 0 and I: 5p 6 . As can be seen from the colour coding, the valence band maximum consists of approximately 70% I 5p and 25% Pb 6s (the Pb 6s forms a band centred around −8 eV), while the conduction band consists a mixture of Pb 6p and other orbitals.…”
Section: A Band Structurementioning
confidence: 99%
“…[1][2][3][4][5][6] They represent the convergence of inorganic thin-film and dye-sensitised solar cells. 7 The conversion efficiencies have quickly surpassed both those of conventional dye-cells, as well as next-generation thin-film absorbers such as Cu 2 ZnSnS 4 .…”
mentioning
confidence: 99%
“…75 A few researchers crafted a unique low temperature processing technique that incorporates an Al 2 O 3 scaffold in a perovskite material. 76 Figure 10(b) illustrates various architectures investigated and efficiencies achieved for hybrid perovskite solar cells. A few researchers reported that increasing the conductivity of the HTMs by doping and optimizing charge collection by adjusting the absorber thickness could bring a positive impact on PCEs in planar heterojunction-based solar cells.…”
Section: Fabrication Proceduresmentioning
confidence: 99%